1991
DOI: 10.1111/j.1365-2761.1991.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Instability of the major soluble antigen produced by Renibacterium salmoninarum

Abstract: Using Western blot to examine the nature of soluble antigens produced by Renibacterium salmoninarum, it was found that the major 57-kilodaIton (kDa) antigen was unstable. SDS-PAGE of extracellular product (ECP) fractions showed that degradation of the 57-kDa protein increased with time and increased temperature. Several lower molecular mass pcptides accumulated temporarily from this degradation. Phenylmethylsuiphonyl fluoride prevented breakdown of the 57-kDa protein suggesting a serine protease present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…In addition, p57 possesses potent immunosuppressive properties which are rapidly lost with the proteolytic degradation of the protein (Rockey et al 1991). Recent studies have demonstrated that the proteolytic degradation of p57 generates most, if not all, of the immunoreactive components of R. salmoninarum ECP and p57 may possess an autoproteolytic activity (Griffiths & Lynch 1991). The N-terminal sequence of p57 has been determined and gene msa encoding this protein has now been cloned and sequenced (Chien et al 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, p57 possesses potent immunosuppressive properties which are rapidly lost with the proteolytic degradation of the protein (Rockey et al 1991). Recent studies have demonstrated that the proteolytic degradation of p57 generates most, if not all, of the immunoreactive components of R. salmoninarum ECP and p57 may possess an autoproteolytic activity (Griffiths & Lynch 1991). The N-terminal sequence of p57 has been determined and gene msa encoding this protein has now been cloned and sequenced (Chien et al 1992).…”
mentioning
confidence: 99%
“…3). The production of MBP-p57, either within the cytoplasm (pMC57HS) or following export to the periplasmic space (pMP57SX) of Escherichia coli XL1-Blue, was accompanied by considerable (Griffiths & Lynch 1991) although this has been associated with the presence of a serine protease of molecular mass about 105 kDa by other workers (Rockey et al 1991). Further examination of the amino acid sequence for p57 which was derived from msa (Chien et al 1992) revealed the presence of a consensus serine protease motif, G-X-S-X-G, located from Gly-406 to Gly-410 (GTSIG) with Asp-323 and His-279 completing the active site (Aitken 1990).…”
mentioning
confidence: 99%
“…However, further studies would need to be conducted to discount the possibility of a comigrating protease. If such autolytic activity can be confirmed, the 72 kDa antigen may be similar to that the 57 kDa major antigen of Renibacterium salmoninarum, the aetiologic agent of bacterial kidney disease (Griffiths & Lynch 1991). Further characterisation of the autolytic behavior and substrate •: sequence deletion; -: conservation of an amino acid;…”
Section: Discussionmentioning
confidence: 98%
“…This mechanism requires p57 to posess proteolytic activity. Lynch and collegues have demonstrated that p57, and several lower molecular weight products of p57, continue to degrade during 2-dimensional electrophoretic separation of ECP (Gnffiths & Lynch 1991, Barton et al 1997. Furthermore, p57, and degradation products of p57 isolated from the WC strain of Renibacterium salrnoninarum, comigrate with PMSF-sensitive proteolytic activity detected by gelatin substrate gels.…”
Section: Fraction (Ml)mentioning
confidence: 99%